HUBUNGAN SELF CARE DENGAN KUALITAS HIDUP LANSIA DI DUSUN KEMBANG KABUPATEN SLEMAN YOGYAKARTA - Maryati Fatukaloba; Nasiatul Aisyah Salim (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2023)
The world’s elderly population is increasing. By 2050, 80 % of the elderly will live in middle an low income countries. So it becomes a challenge because old age becomes a problem when the elderly cannot do basic things. Self care is often used as an index to measure functional capacity in the elderly. Self care is defined as the daily tasks necessary to maintain an independent life or to survive. The decrease in activities of daily living or self care not only has a negative impact on physical well being but also on the social, emotional and mental well being of the elderly. Dependent activities of daily living have a correlation with poor quality of life. So it is necessary to ensure a better quality of life for the elderly, especially because the elderly are more susceptible to disease. The purpose of the study was to determine the relationship between self care and the quality of life of the elderly. This type of research is an analytic observational study with a cross sectional design. The population is the elderly aged 60 years and over as many as 85 people in Kembang Hamlet, Wonokerto Village, Yogyakarta. The sampling technique is total sampling. Data collection techniques used self care and quality of life questionnaires from the world health organization’s quality of life instrument. Data analysis using spearman rank test. The results of this study explain that there is a relationship between self care and the quality of life of the elderly. Suggestions for this study need resilience for the elderly such as self concept, self esteem, coping with emotions, social support, family and community, and life goals.